Improving the framework for assessment of ecological change in the Arctic: A circumpolar synthesis of freshwater biodiversity. (30th December 2021) - Goedkoop, Willem; Culp, Joseph M.; Christensen, Tom; Christoffersen, Kirsten S.; Fefilova, Elena; Guðbergsson, Guðni; Lárusson, Kári Fannar; Liljaniemi, Petri; Novichkova, Anna A.; Ólafsson, Jón S.; Sandøy, Steinar; Lento, Jennifer
Abstract: Climate warming and subsequent landscape transformations result in rapid ecological change in Arctic freshwaters. Here we provide a synthesis of the diversity of benthic diatoms, plankton, macrophytes, macroinvertebrates, and fish in Arctic freshwaters. We developed a multi‐organism measure of α diversity to characterise circumpolar spatial patterns and their environmental correlates, and we assessed ecoregion‐level β diversity for all organism groups across the Arctic. Alpha diversity was lowest at high latitudes and elevations and where dispersal barriers exist. Diversity was positively related to temperature, and both temperature and connectivity limited diversity on high latitude islands. Beta diversity was highly variable among ecoregions for most organism groups, ranging from 0 (complete similarity) to 1 (complete dissimilarity). The high degree of dissimilarity within many ecoregions illustrates the uniqueness of many Arctic freshwater communities. Northward range expansion of freshwater taxa into Arctic regions may lead to increased competition for cold‐stenothermic and cold‐adapted species, and ultimately lead to the extinction of unique Arctic species. Societal responses to predicted impacts include: (1) actions to improve detection of changes (e.g., harmonised monitoring, remote sensing) and engagement with Arctic residents and Indigenous Peoples; and (2) actions to reduce the impact of unwanted changes (e.g., reductions of CO2 emissions, action against the spread of invasive species). Current Arctic freshwater monitoring shows large gaps in spatial coverage, while time series data are scarce. Arctic countries should develop an intensified, long‐term monitoring programme with routine reporting. Such an approach will allow detection of long‐term changes in water quality, biodiversity, and ecosystem services of Arctic freshwaters.